2017
DOI: 10.1080/07481187.2017.1329760
|View full text |Cite
|
Sign up to set email alerts
|

What determines supportive behaviors following bereavement? A systematic review and call to action

Abstract: Very few factors that impact the grieving process can be modified after the fact to the extent that social support can. However, social support has received limited research attention, resulting in little conceptual understanding of the mechanisms behind perceptions of, and intentions to support, grieving persons. This systematic review aimed to explore bereaved, decedent, and respondent-related determinants of the provision of social support. The review yielded 42 studies impacted by various methodological an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
(5 reference statements)
4
47
4
1
Order By: Relevance
“…Through these implicit rules, a dichotomy is created where a loss is either appraised as enfranchised (legitimizing displays of emotion and with the offer of social support) or disenfranchised (where others will not recognize or validate the loss, and support will not be offered; Doka, 2002). How these rules will apply to any given person depend on a complex interplay of factors relating to the deceased (and their manner of death), the bereaved, and the potential supporter (Logan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through these implicit rules, a dichotomy is created where a loss is either appraised as enfranchised (legitimizing displays of emotion and with the offer of social support) or disenfranchised (where others will not recognize or validate the loss, and support will not be offered; Doka, 2002). How these rules will apply to any given person depend on a complex interplay of factors relating to the deceased (and their manner of death), the bereaved, and the potential supporter (Logan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two decades ago, Calhoun and Allen (1991) produced a literature review of 17 studies which identified three participant-related factors (age, gender, bereavement experience) and four decedent-related factors (age, gender, cause of death, family composition) that determined social reactions to suicide bereavement. Logan et al (2017) conducted a systematic review of the entire bereavement literature and identified 42 studies yielding six participant-related factors (gender, bereavement experience, normative beliefs, current bereavement status, age, and familiarity with cause of death), five decedent-related factors (cause of death, anticipation of death, gender, age, and motive for suicidal death), and five bereaved-related factors (gender, time since death, relationship to the deceased, perception of coping, and perceived social support). This review highlighted significant methodological 6 flaws and omissions in this research base, including inconsistent outcome measures with poor or no psychometric properties, little to no control of extraneous variables, nonrepresentative samples, and low power to detect possible relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this research suggest that professionals supporting those who have been bereaved through sudden and/or violent causes, and especially those bereaved through suicide, should consider how the quantity and quality of available informal social support could be increased as a potential means to improve outcomes for their service users [19].…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…Informal social support is therefore the most accessable and personalisable type of support available to those bereaved through violent and/or unexpected causes [19]: interventions to improve access to informal social support for people in this situation could therefore be valuable if its relationship to higher levels of wellbeing is established in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Štaviše, nemali broj poruka koje tugujući dobijaju od njihove socijalne mreže može da nanese više štete nego koristi (Bodie et al, 2010). Da bi socijalna podrška bila efikasna, neophodno je da pojedinac koji želi da je pruži prvo prepozna potrebu za njom, zatim da bude sposoban i voljan za ovu vrstu pomagačkog ponašanja, a kao najbitnije, nužno je da primalac percipira pokušaj pomoći kao koristan i (koliko god je to moguće) utešan vid komunikacije (Logan, Thornton, & Breen, 2018). Pojedini autori navode razne oblike jednoznačno negativnih, pa i povređujućih reakcija koje određene tugujuće osobe doživljavaju od strane prirodnih "pomagača".…”
Section: Uvodunclassified